Effect of short one-third lower face toward mastication performance in Deutero Malay - Anggraeni, Dian; Oewen, Roosje Rosita; Runkat, Jakobus; Hidayat, Syarief (Padjadjaran Journal of Dentistry, 2014)
The one-third lower face height belongs to ideal proportion, ratio 1:1:1, of vertical face height. The one-third lower face height could be influenced by mastication. The one-third lower face height that shorter than normal ratio is generally followed by deep bite which may lead to temporomandibular disfunction even so eustachian tube disfunction, this condition may interfere mastication function, which can be measured by mastication performance. The research objective was to determine the effects of short lower face height to the mastication performance based on overbite. The research method was a cross-sectional study with epidemiology survey type. Research subjects 12-15 years old junior high school with Deutero Melayu Sub races in Bandung. Sampling technique used multistage random sampling by determining the size of the sample based on potluck sample and gained 24 children (group 1) with the normal ratio of vertical face height and 27 children with short lower facial height which were 11 children overbite normal (group 2) and 16 children deep bite (group 3). Mastication performance by 20 times chewing artificial test food then followed by sieving test. Mastication performance value represented by the median particle size (MPS) and the distribution of the particle distribution (b). The results of average MPS and b between group 1, 2 and 3 used statistical analysis MPS with ANOVA test which Fhit=5.56 and pvalue=0.0075, b which Fhit=3.41 and pvalue=0.0430 showed significant differences. Continued with group T test MPS (value = 0.0925) dan b (value = 0.2076) between group 1 and 2 showed a non significant differences. While between group 1 and 3 showed a highly significant differences in MPS (value = 0.0037 and  = 0,01) and a significant differences in b (value = 0.0141 and  = 0,05). Conclusions of this study were children with short lower face height and normal overbite did not decrease the mastication performance while children with deep bite decrease the mastication performance.